MODEL EVOLUSI STRUKTUR ILIRAN-KLUANG DAN POTENSI PLAY RESERVOIR REKAHAN BATUAN DASAR DAERAH RIMAU, SUMATRA SELATAN - ARIADY FIRMANSYAH, DIDIT
Iliran-Kluang structure is a paradox inside the Rimau Blok. A major NW-SE trending structure which controlling regional geology frameworks has yet to be geology structure understood. Therefore the main goal of this study is to evaluate evolution model of Iliran-Kluang structure through different tectonic regimes and its impact to petroleum system in Rimau block. Structure mapping and palinspatic reconstruction has been conducted to analyze the evolution and the behaviour of the structure. Most of the deformations histories in the Rimau block are characterized by complicated structural pattern, therefore depend on seismic interpretation only is insufficient to constrain unique structural interpretation. The results and analysis of palinspatic reconstruction indicate that there are two deformation styles observed across study area. The deformation are extension event occurred from Pre-Tertiary to MFS-10 at Early Miocene then the shortening event occurred after SB-11 at Middle Miocene. Strain analysis of both deformations phase within the basin indicate variation of strain values. The extensional and shortening strain axes consistently show relative NE-SW and NW-SE of direction both during extension and contractional deformations. Therefore, the evolution of basin and structures in the Iliran-Kluang are closely relate to continuous strike-slip fault system from Pre-Tertiary to Recent time. The exposure of Iliran High basement area during syn-rift and poly-phase deformations over the region has increased the potency of fractured basement reservoir developed in the area. An exploration play concept of fractured basement reservoir has been build to summarize all petroleum system components which have to be considered to explore this unconventional play.